Analysis of Crisis Communication Regarding of One-Sided Insurance Claim By Pridential Indonesia - Muhammad Alviansyah Hidayat; Ruth Novarefie Putri Paath; Alya Adninta; Falcao Falcao; Hayunaji Hayunaji (Green Publisher Indonesia, 2025)
Prudential Indonesia's crisis communication strategy in dealing with customer lawsuits against unilateral claim cancellation is categorized as a preventable crisis. Using the Situational Crisis Communication Theory (SCCT) and Image Restoration Theory frameworks, this study evaluates Prudential Indonesia's steps in responding to crises, managing reputation, and restoring public trust. The research method used is qualitative descriptive with a case study approach, involving the analysis of online media news content, social media, and related documents. The results of the analysis show that Prudential Indonesia took good steps through a quick and appropriate response to comply with the Constitutional Court's decision and improve policies related to claims management and procedural transparency. However, weaknesses in the form of a lack of transparency and protection for customers still risk raising public dissatisfaction with Prudential Indonesia's response which is still too general. The recommendations of this study include increasing the transparency of the claims process, strengthening insurance agent training, adopting the Ex Gratia claims policy, reviewing and adjusting policy terms, improving customer complaint services, and proactively communicating with the public. By implementing this strategy, Telkomsel is expected to mitigate the impact of similar crises in the future and maintain its reputation as a trusted telecommunications service provider in Indonesia.